2019
DOI: 10.1371/journal.pone.0214068
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urbanization on predator and parasitoid insects at multiple spatial scales

Abstract: Landscapes are becoming increasingly urbanized, causing loss and fragmentation of natural habitats, with potentially negative effects on biodiversity. Insects are among the organisms with the largest diversity in urbanized environments. Here, we sampled predator (Ampulicidae, Sphecidae and Crabronidae) and parasitoid (Tachinidae) flower-visiting insects in 36 sites in the city of Rome (Italy). Although the diversity of herbivorous insects in urban areas mostly depends on the availability of flowering plants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 49 publications
2
29
1
1
Order By: Relevance
“…The probability of a butterfly nest to be parasitized by P. confusa decreased significantly with increased proportion of artificial surface, but the proportion of larvae parasitized per nest significantly increases. Other studies have shown that parasitoids suffer from environmental changes such as habitat fragmentation and habitat loss (e.g., [ 12 , 14 , 49 ]). We did not detect a specific effect of fragmentation, but it is highly correlated with the proportion of artificial surface (within a buffer of 100 m radius, R 2 = 0.65, p < 0.001), which has a significant negative impact on the propensity of a nest to be parasitized.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of a butterfly nest to be parasitized by P. confusa decreased significantly with increased proportion of artificial surface, but the proportion of larvae parasitized per nest significantly increases. Other studies have shown that parasitoids suffer from environmental changes such as habitat fragmentation and habitat loss (e.g., [ 12 , 14 , 49 ]). We did not detect a specific effect of fragmentation, but it is highly correlated with the proportion of artificial surface (within a buffer of 100 m radius, R 2 = 0.65, p < 0.001), which has a significant negative impact on the propensity of a nest to be parasitized.…”
Section: Discussionmentioning
confidence: 99%
“…The urbanization at both landscape and local spatial scales generally negatively affect the diversity of predator and parasitoid insects. For instance, the streets and buildings negatively affected the diversity of predators (Ampulicidae, Sphecidae, and Crabronidae) and parasitoids (Tachinidae) in Rome, Italy, because these man-made structures limited the dispersal capacity of these predators and parasitoids 22 . Similarly, local effects (garden size, mulch cover, the height of herbaceous vegetation, and tree and shrub richness) and landscape characteristics of the urban cover within 500 m of gardens affected parasitoid diversity in gardens in three counties of the California central coast: Santa Cruz, Santa Clara, and Monterey 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, local effects (garden size, mulch cover, the height of herbaceous vegetation, and tree and shrub richness) and landscape characteristics of the urban cover within 500 m of gardens affected parasitoid diversity in gardens in three counties of the California central coast: Santa Cruz, Santa Clara, and Monterey 20 . Notably, most predators and parasitoids that survive in urbanized landscapes are habitat generalist species and are thus tolerant to the urbanization process 19 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Phillips et al (2019) recorded an average of 61% fewer pollinators along high-traffic roads (1200-1400 vehicles/h) compared to low-traffic roads (0-200 vehicles/h) and (compared to 10 m from the road edge) 70% fewer pollinators 1 m from the road and 59% fewer pollinators 5 m from the road edge. Corcos et al (2019) observed that tachinid fly density and species richness decreased with road proximity in urban areas. The potential drivers of these patterns are difficult to disentangle and could be due to pollinators being repelled by pollution, pollinator population being depleted by pollution, or confounding factors such as pollinator populations being depleted by vehicle-pollinator collisions or resource quality being lower closer to roads.…”
Section: Q4) How Much Does Road Pollution Affect Pollinators?mentioning
confidence: 97%
“…impacting flowers) lethal or sublethal effects. Some observational studies have reported fewer pollinators closer to roads (Corcos et al, 2019;Phillips et al, 2019) and along roads with greater traffic densities (Martin et al, 2018;Phillips et al, 2019), where pollution is likely to be greater. Five studies on butterflies (Flick et al, 2012;Munguira and Thomas, 1992;Skórka et al, 2013Skórka et al, , 2018Valtonen et al, 2006b) and one on bees (Hopwood, 2008) found no such trends (Flick et al, 2012;Hopwood, 2008;Munguira and Thomas, 1992;Skórka et al, 2013Skórka et al, , 2018 though most studies only measure and assess traffic volume as a covariate.…”
Section: Q4) How Much Does Road Pollution Affect Pollinators?mentioning
confidence: 99%